Psychological distress of children with early‐onset type 1 diabetes and their mothers' well‐being. (23rd September 2015) - Hannonen, Riitta; Eklund, Kenneth; Tolvanen, Asko; Komulainen, Jorma; Riikonen, Raili; Delamater, Alan M.; Ahonen, Timo
Abstract Aim Few studies have focused on the psychological adjustment of pre‐adolescent children with type 1 diabetes. This study examined psychosocial functioning in nine‐ and 10‐year‐old children with early‐onset type 1 diabetes, and their mothers, and associations between psychosocial functioning and diabetes management. Methods The mothers of 63 children with early‐onset diabetes and 86 healthy children evaluated their own psychosocial functioning, and their child's, with standardised rating scales. We used general linear models to analyse the children's behaviour problems and the mothers' well‐being. Associations between the children's behaviour problems, diabetes‐related measures and the mothers' well‐being were studied with partial correlations. Results Children with diabetes had more internalising problems than the controls (p = 0.001), and these were associated with poor glycaemic control at the early stage of the illness (p = 0.033) and the use of insulin pumps in girls (p = 0.004). Mothers in the diabetes group had more child‐related stress than the controls (p < 0.001), and poorer well‐being was associated with the children's behavioural problems (p < 0.024). Conclusion Children with early‐onset diabetes faced an increased risk of internalising problems in middle childhood. The mothers' psychological distress was associated with children's behaviour problems rather than their diabetes.